2013
DOI: 10.4314/gjass.v12i1.9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of soil and associated nutrient loss from gully erosion features in Mubi area, Adamawa State-Nigeria

Abstract: A study on the economic analysis of soil and associated nutrients conceded to gully erosion at six sublocations within Mubi area, Adamawa state during the 2007 and 2008 wet seasons. Soil and nutrient loss parameters that related to water erosion were studied in the field, alongside determination of some relevant physico-chemical properties in the laboratory. Relative percentages and tables were used to compare the results. The study revealed an alarming estimates of soil mass and associated nutrient loss in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
2
3
0
Order By: Relevance
“…The results in Table 8 presents a similar economic analysis of the quantity of soil loss by gully erosion as reported by [46] in the same Mubi region. However, such economic analysis on erosion-related researches has not yet been reported, apart from those reported by [46].…”
Section: Soil Science -Emerging Technologies Global Perspectives and Applicationssupporting
confidence: 64%
See 3 more Smart Citations
“…The results in Table 8 presents a similar economic analysis of the quantity of soil loss by gully erosion as reported by [46] in the same Mubi region. However, such economic analysis on erosion-related researches has not yet been reported, apart from those reported by [46].…”
Section: Soil Science -Emerging Technologies Global Perspectives and Applicationssupporting
confidence: 64%
“…The results in Table 8 presents a similar economic analysis of the quantity of soil loss by gully erosion as reported by [46] in the same Mubi region. However, such economic analysis on erosion-related researches has not yet been reported, apart from those reported by [46]. The results show that locations such as the Muvur site with wider and/or deeper gullies recorded larger soil removals with proportionate Adapted from [11,32].…”
Section: Soil Science -Emerging Technologies Global Perspectives and Applicationssupporting
confidence: 64%
See 2 more Smart Citations
“…Wrong use of agrochemicals is the most important dangers faced by farmers, products, and environment. It has been indicated that wrong implementation time and dose, improper use, ignoring the security measures and use of additive-free or expired agrochemicals effects aquatic and terrestrial ecosystems and reduces the quality of underground water consumed by human (Nikolaidis et al, 2007;Tekwa et al, 2010).…”
Section: Introductionmentioning
confidence: 99%